(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This paper discusses the dzikir of the tarekat: The path to peace of mind through the seven Naqsyabandiyah lathifah in Kerinci. The purpose of this study was to see the impact of dzikir lathifah on the soul of someone who practices it. The formulation of the problem in this study: 1). How to practice the dzikir of the seven Naqsyabandiyah lathifah in Kerinci 2). How does dzikir of the tarekat lead to peace of mind. This scientific paper uses a qualitative research method with a descriptive analytical method, a research method that aims to describe and analyze the data that has been collected. The results of the study explain that these seven latifah were first introduced by Sheikh Ahmad Naqsyabandi, a Sufi in the 11th century. According to the understanding of the Naqsyabandiyah tarekat in the human body there are seven places (latifah) as the residence of lust which must be cleaned by dzikir as much as 70,000 times by mentioning the asma. Before practicing the practice of dzikir latifah, a student must first perform a bai’at suluk. After that, practice the Naqsyabandiyah latifah dzikir, namely: Lathifah Qalbi, Lathifah This Ruh, Lathifah Sirr, Lathifah Khafi, Lathifah akhfa, Latifatun nafsun natiqah and Latifah kullu jasad. Latifah dzikir has a very extraordinary impact on life, especially for peace of mind.